Archiving Anthropology - Zeitlyn, D (2000)
Using case studies from the continuing work of the Centre for Social Anthropology and Computing at the University of Kent at Canterbury we discuss ways in which the anthropological research process is enhanced or altered through the creation of online archives of fieldnotes and other research material such as photographs, film and the results of their analysis. Dissemination of field data in this manner both enhances academic debate by enabling alternative analysis and provides rich resources for teaching as demonstrated by the experience rich anthropology project